2021
DOI: 10.1111/sltb.12747
|View full text |Cite
|
Sign up to set email alerts
|

Examining decentering as a moderator in the relation between non‐suicidal self‐injury and suicide ideation via cognitive–affective factors

Abstract: Objective Given the high prevalence of self‐injury but low treatment‐seeking among young adults, brief, accessible interventions might help reduce risk of self‐injurious thoughts and behavior in this population. This cross‐sectional study examined the moderating effects of decentering—a cognitive–affective regulation strategy—in the relation between non‐suicidal self‐injury (NSSI) and suicide ideation via cognitive–affective factors that increase risk for both NSSI and suicide ideation. Methods College student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Authors demonstrated a significant moderated-mediation model for rumination, but not for hopelessness or depressive symptoms. At low and average levels of decentering, there was an indirect effect on the NSSI and SI relationship via rumination, but this association did not hold at high levels of decentering (Rosario-Williams et al, 2021).…”
Section: Studies Related To Cognitive And/or Affective Factorsmentioning
confidence: 84%
See 1 more Smart Citation
“…Authors demonstrated a significant moderated-mediation model for rumination, but not for hopelessness or depressive symptoms. At low and average levels of decentering, there was an indirect effect on the NSSI and SI relationship via rumination, but this association did not hold at high levels of decentering (Rosario-Williams et al, 2021).…”
Section: Studies Related To Cognitive And/or Affective Factorsmentioning
confidence: 84%
“…Paralleling the lack of empirical literature evaluating the Interpersonal Theory of Suicide, few studies have examined the additional theorized associations outlined in Hamza and colleagues' (2012) Integrated Model, including the likely effect of intrapersonal distress on the NSSI -SSI association. The few studies identified in the review (i.e., Anestis et al, 2011;Anestis et al, 2013;Knorr et al, 2016;Rosario-Williams et al, 2021) suggest that, in line with the Integrated Model, several constructs related to intrapersonal distress serve to strengthen the role between NSSI and suicide-related outcomes. However, research has yet to replicate any given association (i.e., only one study examined the role of distress tolerance), limiting the generalizability of these findings.…”
Section: Integration Of Findings Into Theoretical Modelsmentioning
confidence: 98%
“…Dialectical behavior therapy-skill training (DBT-ST), including mindfulness, emotion regulation, distress tolerance, and effective interpersonal relationships, can be effective in reducing self-harm and suicide [ 36 ]. The core mechanism of mindfulness therapy, decentering, involves perceiving situations from a distant “dispassionate observer” state instead of viewing the situation from self-immersed perspective [ 37 ]. This helps to alleviate the direct relationship between NSSI and rumination, thereby influencing the Emotional Cascade Mode.…”
Section: Discussionmentioning
confidence: 99%
“…This helps to alleviate the direct relationship between NSSI and rumination, thereby influencing the Emotional Cascade Mode. It may also reduce the vulnerability of adolescents with moderate to severe NSSI to the transition from rumination to suicidal thoughts and potential suicidal behaviors [ 37 ], potentially stopping the gateway from self-harm to suicide. Considering that the self-harming adolescents in this study showed a higher tendency for rumination, difficulty with distraction, and difficulties with emotion regulation than the control group, DBT-ST may be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the interpersonal model of NSSI (Prinstein et al, 2009) posits that negative interpersonal experiences (e.g., rejection or exclusion) and related mental health problems can predict NSSI. Studies also indicated that perceived discrimination, social support, and depressive symptoms could predict NSSI among adolescents and young adults (Forrester et al, 2017; Rojas‐Velasquez et al, 2021; Wang, Zhang, et al, 2021), which could eventually result in suicidal ideation (Chu et al, 2018; Rosario‐Williams et al, 2021). However, few previous studies contrasted the specific pathways above between impoverished and nonimpoverished students.…”
Section: Introductionmentioning
confidence: 99%